Respostas

2013-10-13T12:51:15-03:00
A = x +2
B = 3x + 4
C = -5x + 1
D = -x + 6
E = x² - x + 2
F = -3x² + 3x + 4

a) a + b
A = x +2
B = 3x + 4
x+2+3x+4
4x+6

b) a + b - c
A = x +2
B = 3x + 4
C = -5x + 1
x+2+3x+4-(-5x+1)
4x+6+5x-1
9x+5

c) e - d
D = -x + 6
E = x² - x + 2
x²-x+2-(-x+6)
x²-x+4+x-6
x²+10

d) a x c - f
A = x +2
C = -5x + 1
F = -3x² + 3x + 4
(x+2)(-5x+1) -3x²+3x+4
-5x²+x-10x+2-3x²+3x+4
-8x²+x-10x+2+3x+4
-8x²+4x-10x+6
-8x²-6x+6

e) f - e
E = x² - x + 2
F = -3x² + 3x + 4
-3x²+3x+4+x²-x+2
-2x²+3x+4-x+2
-2x²-2x+6